Integrasi Lintas Disiplin Ilmu dalam Pembelajaran Tematik - Najwa Sajia El Yunusi; M. Ishom Fahmi Ayatillah; Muhammad Fahmi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2026)
This article discusses cross-disciplinary integration and its application in thematic learning as a holistic approach to shaping a generation that is knowledgeable, faithful, and moral. The dichotomy between religious and general knowledge that is still apparent in the education system has caused an imbalance in the development of students' rational and spiritual abilities. Therefore, Islamic education seeks to restore the epistemological unity between revelation and reason, faith and knowledge, and the spiritual and rational dimensions through an integrative approach in thematic learning. This study uses a library research method with a descriptive qualitative approach, which focuses on the analysis of various related literature. The results of this discussion show that cross-disciplinary integration is the foundation for uniting revelation and reason in the development of Islamic learning models. On the other hand, thematic learning becomes a means of applying the concept of integration by combining various disciplines into themes that are relevant to the lives of students. The result of the collaboration between scientific integration and thematic learning is the creation of an Islamic education model that not only strengthens cognitive aspects but also fosters spiritual, moral, and social character. Thus, this collaboration is a strategic step towards realizing holistic, humanistic, and transformative Islamic education to respond to the challenges of the modern era.